Caribbeanness: a Diasporic State of Collision and Dialogue - Beroiz, Luciana (2006)
In Routes: Travel and Translation in the Late Twentieth Century, James Clifford defines "diaspora consciousness" as "entirely a product of cultures and histories in collision and dialogue (...) a site of multiple displacements and rearticulations of identity"(1997: 266). The Caribbean, with its history of colonialism and slavery, decolonization and migration, becomes the perfect space for the analysis of the development of this diasporic identity. Marked by a "a painful pattern of confrontations and ruptures" and "considerable mutations of personal and cultural identity"(Balutansky 1998: 5), the concept of Caribbeanness has been, and is still, determined by a constant movement which has led to the cultural integration and juxtaposition of the African, the Indian, the Asian and the European. A large number of 20th century Caribbean artists and theorists have made the analysis of this 'movement' and its effects on both Caribbean identity and discourse central to their narratives. This study concentrates on how Aimé Césaire, Marlene Nourbese Philip and George Lamming represent the realities of 'movement' in their respective diasporic cultures. Their narratives take us on a trip to a revision of a history of slavery and exploitation and the recovery of a repressed past through the re- membering of African culture and roots.